Experimental assessment of chloride and sulfate ions on the durability of CO2 carbonated backfill materials - Ichhuy Ngo; Ruizhi Yang; Kunpeng Yu; Zhiyang Zhao; Kaidan Zheng; Zhishang Zhang; Chengkun Peng; Hemeng Zhang (PLoS ONE, 2026)
The present study investigates the durability of CO 2 -carbonated coal-based solid waste backfill materials under the deterioration effects of chloride and sulfate ions. The primary objective is to evaluate the feasibility of environmentally favorable, CO 2 negative backfilling materials for application in coal mining goaf stabilization. Carbonated samples at various curing stages were immersed in chloride and sulfate solutions, with tap water serving as the reference medium. Several key aspects were assessed, including dimensional alterations, mechanical property variation, phase evolution, and microstructural characteristics. Key phases were identified via XRD and SEM-EDS. The results indicate that the degree of deterioration followed the order: Cl - > tap water> SO 4 2- . Compared with tap water, chloride exposure caused more severe degradation, whereas sulfate exposure partially mitigated the deterioration. Compressive strength decreased by 43.9% and 20.6% after immersion in chloride and sulfate solutions, respectively. The pronounced difference in damages is attributed to the high diffusivity of chloride ion with concentrations approximately 2.5 times higher than sulfate ions at a 5 mm depth, which not only consumed CaCO 3 and C-A-S-H gel but also promoted the formation of Friedel’s salt and facilitated anion exchange reactions. In contrast, sulfate exposure led to the formation of ettringite crystals after leaching, which, when maintained below a certain concentration, acted as a filling agent that reduced microstructural porosity. This study provides a fundamental insights into the performance of CO 2 -carbonated backfill materials in chloride- and sulfate-rich environments, offering guidance for their practical application in sustainable coal mine backfilling.